Answer:
1) (2x + 2)(x + 2)
2) 2(x + 1)(x - 1)
3) (x^2 + 3)(x^2 - 3)
4) 2x(x + 5)(x - 2)
5) (5x + 2y)(5x - 2y)
Step-by-step explanation:
1)
2x^2 + 6x + 4
= 2x^2 + 4x + 2x + 4
= 2x(x + 2) + 2(x + 2)
= (2x + 2)(x + 2)
2)
2x^2 - 2
= 2(x^ 2 - 1) (The difference of two squares)
= 2(x + 1)(x - 1)
3)
x^4 - 9 (The difference of two squares)
=(x^2 + 3)(x^2 - 3)
4)
2x^3 + 6x^2 - 20x
= 2x(x^2 + 3x - 10)
= 2x(x + 5)(x - 2)
5)
25x^2 - 4y^2 (The difference of two squares)
= (5x + 2y)(5x - 2y)
7^(-3) = 1/7^3 = 1/343
- 7^3 = - (7^3) = -343
As can be seen, the results are very different.
Answer:
31 trillion
Step-by-step explanation:
31 trillion
It was shattered by a Google employee about 5 days ago
First, you have to simplify the equation:
y+3 = 3(x+5)
y+3=3x+15
So you multiply what’s inside the brackets (x+5) by the factor (3). So 3•x=3x, 3•5=15.
Then you rearrange the equation as necessary to convert it into standard form, which is Ax + By = C
Answer:
You can start with any statement in the form a = a. Then add the same variable term to both sides, and add the same constant term to both sides. Combine like terms on each side.
Step-by-step explanation:
i got this online i hope it helps